Assessing the impact of software quality models in healthcare software systems. Issue 1 (2nd January 2023) - Ronchieri, Elisabetta; Canaparo, Marco
ABSTRACT: Health and medical care are safety-critical environments. The development of a safe and reliable healthcare software system is one of the most important processes which may affect the accuracy of clinical decision making and have an impact on determining diagnoses of and treatment for diseases. The aim of this study is to assess if software quality models, such as McCall, can have an impact on healthcare software quality for the purpose of reducing software failures. We have identified the main criticalities of healthcare software systems based on existing literature, software quality models and programming language standards; we have related these criticalities to software characteristics; we have analysed the relationship between the main criticalities of healthcare software systems and their software characteristics. The following criticalities - the risk of changing hard-coded software and the importance of developing maintainable software – must be addressed at the start of the software development process.